Inverse kinematics and control of 4-degree-of-freedom wire-actuated in vivo robot. (February 2015) - Sutar, MK; Pathak, PM; Mehta, NK; Sharma, AK; Gupta, VK
Endoscopes have been in use for many clinical procedures including biopsy and limited surgery. A biopsy is one of its most common applications. For more than a decade, research is in continuation on various limitations encountered by surgeons in this area like dexterity, manoeuverability and controlling of the scope tip to bring it to an exact point of interest. Existing endoscopes have limitations in number of degrees of freedom. To counter this problem, a 4-degree-of-freedom in vivo robot has been proposed by the authors earlier. This article presents an inverse kinematic solution of the wire-actuated in vivo robot for trajectory control. For this, a kinematic analysis has been performed and the tip positions were obtained analytically. For a known tip position, the length of the wire to be wrapped and un-wrapped is decided from the relational approach and accordingly the desired pulley rotation is performed using the proportional–derivative controller. Simulations have been carried out for three different cases and satisfying results were obtained.